A new species of Mikania (Asteraceae, Eupatorieae) from the Western Cordillera of Colombia - Aguilar-Cano, José; Díaz-Piedrahíta, Santiago (Phytotaxa, 2015)
A new species of Mikania from the northern area of the Western Cordillera of Colombia is described and illustrated. Taxonomic affinities with its closest relatives M. lloensis and M. flabellata are discussed. The diagnostic traits of the new species are: the long peduncle of the synflorescence; the size of the head; the presence of a midvein in the corolla lobes; the presence of moniliform, multicelular, uniseriate trichomes below the commissural sinuses of the corolla lobes; the insertion of the stamens at the mid-level of the hypocrateriform corolla; and the retuse apical appendages of the anthers. The latter trait is newly used here as diagnostic in the genus.